Impact of a medical university on laparoscopic surgery in a service-oriented public hospital in the Caribbean - Cawich, Shamir O (Risk Manag Healthc Policy, 2016)
INTRODUCTION: The Caribbean lags behind global trends for volume and complexity of laparoscopic operations. In an attempt to promote laparoscopy at a single facility, a partnership was formed between the University of the West Indies (UWI) and the Port of Spain General Hospital in Trinidad and Tobago. This study seeks to document the effect of this partnership on laparoscopic practice. MATERIALS AND METHODS: In this partnership, the UWI took the bold step of volunteering to staff a surgical team if the Ministry of Health provided the necessary legislative changes. On August 1, 2013, a UWI team was introduced with a mandate to optimize teaching and promote laparoscopic surgery. The UWI team had a similar staff complement to the existing service-oriented teams. There was no immediate investment in equipment, hospital beds, ICU beds, or operating room space. Therefore, the new team was introduced with limited change in existing conditions, resources, and equipment. RESULTS: There were 252 laparoscopic operations performed over the study period. After introduction of the UWI team, there was an increase in the mean number of unselected laparoscopic operations (3.17 vs 10.83 cases per month; P<0.001; 95% confidence interval [95% CI] −8.5 to −6.84; standard error of the difference [SED] 0.408), the mean number of basic laparoscopic operations (3.17 vs 6.94 cases per month; P<0.0001; 95% CI −4.096 to −3.444; SED 0.165), the mean number of advanced laparoscopic operations (0 vs 3.89; P<0.0001), the number of teams undertaking unselected laparoscopic operations (2 vs 5), and the number of teams independently performing advanced laparoscopic operations (0 vs 4). CONCLUSION: At this facility, we have demonstrated a significant increase in laparoscopic case volume and complexity when partnerships were formed between the UWI and this service-oriented hospital. Continued cross-fertilization and distribution of skill sets across the surgical community can reasonably be expected. We also identified maneuvers that can be used as a template to build laparoscopic services in other service-oriented hospitals in developing nations.